Interoceptive Deficits, Nonsuicidal Self‐Injury, and Suicide Attempts Among Women with Eating Disorders. Issue 4 (22nd August 2017) - Dodd, Dorian R.; Smith, April R.; Forrest, Lauren N.; Witte, Tracy K.; Bodell, Lindsay; Bartlett, Mary; Siegfried, Nicole; Goodwin, Natalie
Abstract : People with eating disorders (EDs) have an elevated risk for both nonsuicidal self‐injury (NSSI) and suicide compared to the general population. This study tests two theoretically derived models examining interoceptive deficits as a risk factor for NSSI, and examining interoceptive deficits, NSSI, fearlessness about death, and pain tolerance as risk factors for suicide. Ninety‐six adult, treatment‐seeking women with EDs completed self‐report questionnaires at a single time point. Interoceptive deficits were significantly associated with NSSI, and NSSI was in turn associated with both pain tolerance and fearlessness about death. Further, pain tolerance was in turn associated with past suicide attempts, although fearlessness about death was not associated with suicide attempts. Interoceptive deficits had a direct association with fearlessness about death but not pain tolerance. Results regarding the relation between interoceptive deficits and suicide attempts were mixed, yet overall suggest that interoceptive deficits are related to suicide attempts largely indirectly, through the effects of mediating variables such as NSSI, fearlessness about death, and pain tolerance. Results suggest that interoceptive deficits and pain tolerance merit further investigation as potential risk factors for fatal and nonfatal self‐harm among individuals with EDs.